Correlation Between Clinical Factors and Pregnancy Outcome Following Repeat Cerclage: A Retrospective Analysis of a Chinese Population - Cai, Benshuo; Xia, Yajun; Na, Xinni (Frontiers in Medicine, 2022)
Background: The role of repeat cerclage (RC) among patients with prolapsed membranes remains controversial. We aimed to investigate the effectiveness of RC and assess the correlation between clinical factors and pregnancy outcome following RC. Methods: The clinical data of patients who underwent RC for prolapsed membranes after prior cerclage were retrospectively investigated. The clinical characteristics of patients were compared between singleton and twin pregnancies. The clinical characteristics of singleton pregnancies were compared between the gestational age (GA) at delivery <28 weeks’ and ≥28 weeks’ groups. Receiver operating characteristic (ROC) curve analysis was performed to determine predictive factors. Singleton patients were divided into two groups according to GA at RC as follows: GA <22.3 weeks and GA ≥22.3 weeks. Pregnancy outcomes were compared between groups. Results: The mean GA at delivery of singleton pregnancies was significantly higher than that of twin pregnancies. The mean latency between RC and delivery of singleton pregnancies was significantly longer than their twin counterparts. There were significant differences in the pregnancy outcomes between the GA <22.3 weeks group and GA ≥22.3 weeks group. Kaplan–Meier survival curves showed a lower incidence of neonatal death in the GA ≥22.3 weeks group compared with that in the GA <22.3 weeks group. Conclusions: RC may be an effective method to prolong the duration of pregnancy among patients with singleton pregnancy. However, the selection of RC for patients with twin pregnancies remains controversial. GA at RC appears to be fair for predicting pregnancy outcomes following RC.